2017
DOI: 10.4103/sni.sni_68_17
|View full text |Cite
|
Sign up to set email alerts
|

Never say never again: A bone graft infection due to a hornet sting, thirty-nine years after cranioplasty

Abstract: Background:Cranioplasty (CP) is a widespread surgical procedure aimed to restore skull integrity and physiological cerebral hemodynamics, to improve neurological functions and to protect the underlying brain after a life-saving decompressive craniectomy (DC). Nevertheless, CP is still burdened by surgical complications, among which early or late graft infections are the most common outcome-threatening ones.Case Description:We report the case of 48-year-old man admitted to our neurosurgical unit because of a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…There seems to be no significant difference between the two preservation methods. After autologous cranial flap replantation, the adult bone resorption ratio was 3-22% [13][14][15][16][17][18]. Recent literature data suggest that this figure is more complex in children than the 50% complication rate initially described by De Bonis et al and Frassanito et al [18,19].…”
Section: Situations and Challenges Of Autologous Cranioplastymentioning
confidence: 92%
“…There seems to be no significant difference between the two preservation methods. After autologous cranial flap replantation, the adult bone resorption ratio was 3-22% [13][14][15][16][17][18]. Recent literature data suggest that this figure is more complex in children than the 50% complication rate initially described by De Bonis et al and Frassanito et al [18,19].…”
Section: Situations and Challenges Of Autologous Cranioplastymentioning
confidence: 92%
“…To do this, the prosthetic reconstruction phase has an essential role [37]. Recent studies have shown how an appropriate biomechanical reconstruction can cause fewer complications and reduce the risk of re-intervention [18,36,38]. Indeed, 3D-printed custom-made protheses provide anatomical stability and consequently an improved success rate thanks to the vertebral prothesis designed based on the patient's characteristics and anatomy.…”
Section: Surgical Implants and 3d-prosthesismentioning
confidence: 99%
“…Autologous fibrin sealant application during spinal procedures ensures rapid hemostasis and effective dural sealing [52]. During cranial techniques, Vivostat may be used to complete and improve hemostasis on the surgical field, prevent CSF leakage through a reliable dural sealing, and repair dural defect even during skull base surgery [46,[53][54][55]. In conclusion, the use of autologous fibrin would encourage new questions about its biological effects and its possible fields of employment.…”
Section: Fibrin Sealantsmentioning
confidence: 99%